Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) di PT. Karimun Granite - Siska Aprilia; Dadang Mashur (Public Inspiration : Jurnal Administrasi Publik, 2025)
Management in the form of hazardous waste storage activities is one of the activities that need attention from various parties because if hazardous waste is not managed properly, it will increase the potential for harm to the environment and society. This research was motivated by the issue of hazardous waste management practices that do not comply with applicable standards in several industries in Karimun Regency, including Karimun Granite company as one of the companies producing hazardous waste. This study aims to determine the management of hazardous waste at Karimun Granite company and the factors that hinder its implementation. This research uses a qualitative research method with a case study approach. Data collection is done through interviews, observation, and documentation. The results showed that the management of hazardous waste at Karimun Granite company was not optimal. This is viewed from the aspects of plan, do, check, and act; where the management carried out is not by the established plan. The inhibiting factors in the management of hazardous waste at Karimun Granite company are the lack of understanding and awareness of hazardous waste generators, the limited number of personnel managing hazardous waste, lack of infrastructure for hazardous waste management. Therefore, it is necessary to review and take corrective action on each identified deficiency in order to realize hazardous waste management that complies with standards while supporting the creation of a sustainable and environmentally sound industrial climate in Karimun Regency.